Identification and full-genome characterization of novel circoviruses in masked palm civets (Paguma larvata) - Nishizawa, Tsutomu; Sugimoto, Yuji; Takeda, Tsutomu; Kodera, Yuuji; Hatano, Yumi; Takahashi, Masaharu; Okamoto, Hiroaki (Virus Research, 2018)
•We identified 3 novel circovirus genomes from 3 of 10 Paguma larvata in Japan.•The complete nucleotide sequences of the 3 circovirus genomes were determined.•The 3 genomes possessed a unique rep gene with two introns at the 5′-terminus. The family Circoviridae comprises a large group of small, circular, single-stranded DNA viruses and is classified into two genera: Circovirus and Cyclovirus. They have marked genetic diversity and a broad host range. In this study, three novel circovirus genomes were identified from wild-caught masked palm civets (Paguma larvata) in Japan and classified as a new species within the genus Circovirus based on the demarcation criteria of the International Committee on the Taxonomy of Viruses. Of note, the presence of two predicted introns at the 5′-terminus of the rep gene was suggested in the Paguma larvata circovirus genomes.